Assessing and managing scenery of the Caribbean Coast of Colombia (2012)
This study provides the coastal scenery assessment of 135 sites along the Colombian Caribbean littoral by analysing 26 physical and human factors. Sites were categorised into ﬁve classes from Class 1, top grade scenery, to Class 5, poor scenery -- Fifty ﬁve percent of the investigated coastal areas were included in Classes 1 and 2, 18% belonged to Class 3 and 47% of the sites fall into Classes 4 and 5 -- Classiﬁcation of analysed sites depends on the geological setting and the degree of human occupation -- Classes 1 and 2 sites are located in natural protected areas in La Guajira and Magdalena departments -- Low classiﬁcation recorded at Classes 3, 4 and 5 corresponds to a progressive decrease of both natural and (especially) human parameters -- Concerning coastal management issues, emphasis should be given to the upgrading of human parameters eliminating litter and sewage evidences, vegetation debris and enhancing beach nourishment works